Pengembangan Media Animasi Menggunakan Adobe Flash CS5 Untuk Materi Pembelajaran Siklus Hidrologi Pada Mata Pelajaran Geografi Kelas X-IS Sekolah Menengah Atas (SMA) - Andino, Mohammad Pandu (2016)
Recenty, technology has experienced very fast developments, one of them is in the educational field. A teacher as a person who manage the learning activities must be able to use the technology to design and develop media in the learning process. The learning media have a very important role in determining the success of the learning process, in which there have many kinds of learning media today. This research aimed at knowing the criteria, the development process, and the effectiveness of animation learning media of the material of hydrology cycle. The method used in this research was research and development (R&D) that was a research method used to create a certain product and to test the effectiveness of the product with a prosedural stage which referred to the development model of Dick and Carey. The results of the research showed that the criteria of animation learning media must be full color, accompanied by music, have a voice effect, have text/explanation, have motivation, and display the Core Competencies (Kompetensi Inti/KI), and the Basic Competencies (Kompetensi Dasar/KD), and the Learning Objectives, that finally the animation learning media which have been validated by the experts and testified as proper to be used in the learning process are created. The results of experimental research were shown on the average numbers of pretest and post test of the control class (not being given with a special treatment) and the experimental class (being given with a special treatment "animation learning media"), which were 35.36 (the control class) and 34.05 (the experimental class) for the pretest average, 48.29 (the control class) and 66.48 (the experimental class) for the post test average. Based on the test of Mann Whitney, it showed that there was difference in the learning result between the control class and the experimental class, in which the experimental class experienced an average increase as much as 32.43, whereas, the control class only experienced an average increase as much as 12.98, so, the average increase of the learning results the experimental research was higher than the control's one. Therefore, it can be concluded that the use of animation learning media on the material of hidrology cycle is more effective than the conventional learning (no use of learing media).